Black Cutworm Management for Corn in Kansas - Higgins, Randall A.; Sloderbeck, Phillip E. (My University, 2005)
This publication describes the black cutworm and how to manage it in corn production.
MF1105_2005-06
Keywords: MF1105; Insects; Crops; MF